Characterization of natural gas hydrate recovered from Pearl River Mouth basin in South China Sea. (March 2015) - Liu, Changling; Meng, Qingguo; He, Xingliang; Li, Chengfeng; Ye, Yuguang; Zhang, Guangxue; Liang, Jinqiang
Abstract: China carried out a drilling campaign in the eastern part of the Pearl River Mouth (PRM) basin and successfully obtained natural gas hydrate samples in 2013. Laboratory based studies for the characteristics of gas hydrate were carried out on one of the hydrate-bearing sediment sample. The gas hydrate sample shows nodular occurrence with host matrix predominantly composed of silty sand and clay. On the basis of the Raman spectroscopic and X-ray diffraction results, the gas hydrate demonstrates a typical structure I (sI) with cage occupancy of methane is more than 99.5% in large cage and 91.4% in small cage, respectively, corresponding to a hydration numbers of 5.90 by thermodynamic calculation. The molecular compositions of hydrate-bound gas suggest that the guest molecules are predominantly methane (>99.9%), with trace amount of ethane (0.04%) and propane (0.01%). The isotopic analysis indicates that the methane of hydrate-bound gas of the studied drilling well in PRM basin is a typical microbial origin. Graphical abstract: Highlights: The characteristics of gas hydrate from PRM basin were firstly reported. Very fine grain of sediment can't support pore-filling gas hydrate formation. The gas hydrate is typical cubic structure I with unit cell parameter of 11.9338 Å. Both large and small cages are well occupied with a hydration number of 5.9. The hydrate-forming gas is predominantly CH4 of microbial origin.